Edukacja techniczna młodzieży – priorytet czeskiego systemu oświaty w XXI wieku - Vališová, Alena (Studia Edukacyjne, 2020)
The presented text conceptually proceeds from the strategic and conception documents of the Czech Ministry of Education (MŠMT) and includes among the priority objectives primarily the openness to the new methods and manners of teaching by means of digital technologies, improvement of pupils’ competences of working with information and digital technologies and, last but not least, the development of pupils’ IT thinking. The motivation for secondary school students’ choice of technical bran-ches is regarded as a priority orientation of the contemporary school system in the Czech Republic.